2002
DOI: 10.2214/ajr.178.2.1780445
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Detection of Lymph Nodes in the Intussusception of Infants and Young Children

Abstract: Enlarged lymph nodes in the intussusception are mainly found in patients with a current or recent history of gastroenteritis and decrease the overall hydrostatic reduction rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…The presence of at least two intussuscepted lymph nodes, of which one measures a minimum of 11 mm in diameter, is more common in children with current or recent history of gastroenteritis and is related to a lower hydrostatic reduction rate [34].…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…The presence of at least two intussuscepted lymph nodes, of which one measures a minimum of 11 mm in diameter, is more common in children with current or recent history of gastroenteritis and is related to a lower hydrostatic reduction rate [34].…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Sonologic detection of pneumatosis intestinalis in combination with other findings such as bowel wall ischemia (no flow on Doppler), peritoneal fluid and enlarged lymph nodes on the ultrasound may prognosticate failure of non-surgical reduction of intussusception. [14, 19]. Detection of pneumatosis intestinalis has also implications on early detection of enterocolitis especially in premature neonates presenting to the ED with gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Per their study enlarged lymph nodes are found in patients with a current or a recent history of gastroenteritis and correlate with a lower overall hydrostatic reduction rate [5]. Del-Pozo et al evaluated fluid, seen inside the intussusception, which represented trapped peritoneal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Various US signs (trapped peritoneal fluid [3], absence of blood flow [4], enlarged lymph nodes [5]) predict a lower likelihood of image guided hydrostatic or pneumatic reducibility. These ultrasound findings correlate with a lower likelihood of reduction ranging from a reduction rate of 0% for peritoneal fluid (>14mm × 5 mm) to a reduction rate of 40% for enlarged lymph nodes (8.1mm – 11mm) [3, 5]. The generally accepted contraindications remain shock, sepsis, peritonitis and free gas [68].…”
Section: Introductionmentioning
confidence: 99%